Pengaruh Work Life Balance Dan Burnout Terhadap Kepuasan Kerja Karyawan Pada The Westin Resort Nusa Dua Bali - Wirayani, I Gusti Ayu Agung; Sulistyawati, Ni Luh Ketut; Kalpikawati, Ida Ayu (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2025)
Employee job satisfaction can be conceptualized as a cognitive–affective equilibrium emerging from an individual’s interpretative appraisal of multifaceted occupational dimensions. This construct does not occur in isolation but is contingent upon a constellation of antecedent variables, notably work-life balance and occupational burnout. The principal objective of this inquiry is to empirically elucidate the directional influence exerted by work-life balance and burnout upon the experiential state of job satisfaction among personnel affiliated with The Westin Resort Nusa Dua Bali. The investigational cohort comprises the entirety of organizational incumbents within the aforementioned hospitality establishment, from which a representative subsample of 218 respondents was derived through a probabilistic selection framework employing proportional stratified randomization. Data interrogation was operationalized via multivariate linear regression modeling to capture simultaneous and discrete effect trajectories. Analytical outcomes substantiate that work-life balance exerts a statistically robust positive association with employee job satisfaction, whereas burnout manifests an inversely proportional and statistically significant relationship with the same construct. Moreover, when entered conjointly into the predictive model, these dual determinants exhibit a significant aggregate effect, cumulatively accounting for approximately 54.5% of the variance observed in employee job satisfaction.